Analisis Perilaku dan Preferensi Wakaf Generasi Milenial Melalui Perbankan Syariah - Muhamad Alim; Maulana Malik Syehudin; Mochammad Izdiyan Muttaqin (ITB AAS INDONESIA Surakarta, 2023)
Inequality and poverty reduction programs in Indonesia require enormous funds which cannot be fully provided by the government, initiating new funding sources for such programs is unavoidable. The Islamic socio-economic system has provided one of the key sources of funds for communities with waqaf. Islamic banks that have an intermediary function as Islamic financial institutions can take an important role as a professional Nadzir partner. The absence of previous research on the behavior and preferences of the millennial generation in waqaf in Islamic banking makes this research feasible to increase the role of Islamic banking and Indonesia's geographical potential in reducing poverty and inequality. The research applies a transdisciplinary science between psychology (behavior and preferences), Islamic economics (waqf) and economics (management). The method used is descriptive quantitative with a Likert scale and random sampling to students or recent graduates at the Department of Islamic Economics, Padjadjaran University as many as 104 respondents and analyzed textually. The results show that the religiosity of the millennial generation is quite high, so that waqaf in Islamic banking is 95%, the reputation of Islamic banking in the eyes of the millennial generation so that they choose waqaf in Islamic banking is 79%, the waqaf procedure in Islamic banking facilitates the millennial and z generations by 71%. , the knowledge level of the millennial generation regarding waqf in Islamic banking is 79%. Keywords: preference, waqaf, and Islamic banks